Combating Vaccine Hesitancy: Teaching the Next Generation to Navigate Through the Post Truth Era - Arede, Margarida; Bravo-Araya, Maria; Bouchard, Émilie; Singh Gill, Gurlal; Plajer, Valerie; Shehraj, Adiba; Adam Shuaib, Yassir (Frontiers in Public Health, 2019)
Despite scientific evidence supporting the fact that vaccines are fundamental tools for preventing infectious diseases, a percentage of the population still refuses some or all of them. Vaccine hesitancy has become a widespread issue, and its complexity lies in the great variety of factors that can influence decisions about immunization, which are not just vaccine-related concerns, but also involve personal and societal levels. Our research group performed an extensive literature review to analyze: (1) different age groups, their relation to the problem and their characteristics; (2) the most important information (key messages) about immunization that could be used to counteract hesitancy; and (3) best approaches to transmit the messages to the target groups. We propose a long-term approach to overcome vaccine hesitancy that involves the education of children and adolescents on the basics about immunization and critical thinking, using different communication channels.